2022
DOI: 10.1021/acscatal.2c02627
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Dynamic Construction of a Copper Tin Sulfide Catalyst for High-Performance Electrochemical CO2 Conversion to Formate

Abstract: Electrochemical reduction of CO 2 to produce fuels and chemicals is one of the most valuable approaches to achieve a carbon-neutral cycle. Recently, a diversity of catalysts have been developed to improve their intrinsic activity and efficiency. However, the dynamic evolution process and the in situ construction behavior of electrocatalysts under the working conditions are typically ignored. Here, we fully reveal the dynamic reduction process and phase transformation of a copper tin sulfide catalyst reconstruc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(38 citation statements)
references
References 56 publications
0
37
0
1
Order By: Relevance
“… In a similar note, the NiS/Ni 2 P heterostructure also retains its pristine morphology after HER, while after OER, an amorphous shell of NiO­(OH) formed . In another study, Cu 2 SnS 3 behaved as a pre-catalyst and a Cu–Sn alloy formation was precedent as the active species under the applied potential . Recent studies on CO 2 R with Cu 2 Se have shown that the presence of Se 2– with Cu­(I) resulted in ligand (Se)-to-metal (Cu) back-bonding, which increases the electron density on Cu to have better CO adsorption .…”
Section: Resultsmentioning
confidence: 99%
“… In a similar note, the NiS/Ni 2 P heterostructure also retains its pristine morphology after HER, while after OER, an amorphous shell of NiO­(OH) formed . In another study, Cu 2 SnS 3 behaved as a pre-catalyst and a Cu–Sn alloy formation was precedent as the active species under the applied potential . Recent studies on CO 2 R with Cu 2 Se have shown that the presence of Se 2– with Cu­(I) resulted in ligand (Se)-to-metal (Cu) back-bonding, which increases the electron density on Cu to have better CO adsorption .…”
Section: Resultsmentioning
confidence: 99%
“…Of note, a substantial oxide phase persists in SnO 2 electrodes during cathodic reactions as manifested by in situ observations. , Consequently, multivalent Sn species including metallic Sn and its oxides are usually involved in SnO 2 -based catalysts, which can contribute synergistic effects for the catalytic process. In particular, the metallic Sn and SnO 2 derived from identical precursors tend to join with each other, forming robust heterogeneous interfaces at the grain boundaries. Because of the unique local coordination environment at interfaces, the electronic structure of Sn atoms can be altered, thereby influencing the intrinsic catalytic activity. In this regard, constructing a heterostructure of metallic Sn and SnO 2 with abundant interfacial boundaries is promising to fabricate an efficient catalyst for CO 2 -to-formate conversion, wherein a uniform distribution of Sn in the SnO 2 matrix is essential. However, aggregation of metallic Sn in situ derived from SnO 2 is thermodynamically more favorable, and modulating the dispersion of Sn in the nanoscale remains challenging.…”
Section: Introductionmentioning
confidence: 99%
“…Both experimental results (high partial current density of −241 mA/cm 2 and high HCOOH FE of 96.4%) and theoretical DFT calculation results evidenced that the strong charge interaction between the adsorbate and the substrate could enhance charge transfer, resulting in reduced energy for the generation of OCHO* and *COOH intermediates. Therefore, high formic acid selectivity was achieved in the catalytic reaction Figure b shows the partial current densities of the products of the different CuS catalysts.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Therefore, high formic acid selectivity was achieved in the catalytic reaction. 41 Figure 9b shows the partial current densities of the products of the different CuS catalysts. As indicated, all the catalysts show high CO partial current density (0.82∼1.70 mA/cm 2 ), and their HCOOH partial current density varies around 0.20∼0.30 mA/cm 2 .…”
Section: Electrochemical Comentioning
confidence: 99%